Bilateral superior lumbar hernias: a case report and review of literature - Radhakrishna, Veerabhadra; Tanga, Sharad M. (International Surgery Journal, 2017)
Primary lumbar hernias are uncommon. They present with backache, flank pain, occasional nausea, feeling of weight or dragging sensation in the lumbar region. When they are small, they may be unnoticed leading to significant morbidity with the patient seeking referrals and therapy with no resolution of symptoms. They should be repaired in time to avoid dreaded complications of obstruction and strangulation. A sixty-year man presented with swelling and pain in the left loin. On evaluation, he was found to have bilateral superior lumbar hernias, which was treated with mesh repair.